Nutritional status, diet and quality of life of acute leukemia patients after induction chemotheraphy in three selected hospitals in Tehran, Iran - Malihi, Zarintaj (2012)
Cancer is rated the 3rd most common cause of death in Iran. Adult leukemia which is a type of cancer in which the bone marrow generates abnormal myeloblasts or lymphoblasts, was ranked the 5th most common type of cancer in Iran in 2005. Chemotherapy is the primary treatment choice for leukemia before deciding for bone transplantation. This study aimed to determine the nutritional status, dietary intake and quality of life (QOL) of adults with Acute Myeloid Leukemia (AML) and Acute Lymphoblastic Leukemia (ALL) during the first stage of chemotherapy also known as induction chemotherapy. To have a clearer understanding of change in nutritional status and Quality Of Life (QOL), patients were assessed twice i.e.before and after the induction stage of chemotherapy. This is a prospective study with pre and post measures on adult leukemia patients which has been rarely reported in the literature. The study subjects were newly diagnosed adult leukemia patients admitted to three main referral hospitals of Tehran, Iran. The Patient Generated Subjective Global Assessment (PG-SGA) used to evaluate nutritional status. Dietary intake was determined using a 136-item validated Food Frequency Questionnaire (FFQ) based on Iranian foods and two days 24-hour diet recall. The European Organization for Research and Treatment on Cancer (EORTC) QOL-C30 version 3 was used to assess four domains of quality of life (Functional scales, symptom scales, single items and global QOL) of patients. A structured questionnaire was used to obtain information on Sociodemographic characteristics and clinical characteristics of the patients. Data collection was done from June 2009 to March 2010. Primary analysis of dietary intake was conducted with Nutritionist IV dietary data analyzer software. Statistical analysis was conducted using SPSS package version 17. Hypotheses were examined using multiple linear regression analysis. Sixty three acute leukemia patients consisting of 30 AML and 33 ALL patients,including 41 men (65.1%) and 22 (34.9%) women were recruited during data collection. Mean age of AML and ALL patients were 40 and 26 years old,respectively. Mean weight of patients before and after first induction was 66 kg and 62kg respectively and mean weight loss was 3.36 ±0.7 kg. A significant change in nutritional status of the patients as well as significant difference in dietary intake indices and quality of life score after chemotherapy was found. Malnutrition increased considerably after chemotherapy from 19.4% to 76.1% moderately malnourished and from 0% to 6.3% of patients who were severely malnourished. The change in nutritional status was not significantly related to change in global quality of life after chemotherapy, although before chemotherapy there was a significant linear relationship (F= 20.55, R2=0.263, P<0.001), indicating that 26.3% of variation in quality of life can be explained by nutritional status. A significant relationship between changes in both total energy intake and food variety score(FVS) of patients and nutritional status was found (F=6.67, R=0.427, R2 =0.182) which explained 18.2% of variation in nutritional status change. It can be concluded that malnutrition occurs significantly in AML and ALL patients during induction chemotherapy and influences the quality of life during induction of chemotherapy which is may inversely affect remission rate and treatment outcome. Dietary intake changed after chemotherapy significantly and was linearly correlated with nutritional status of patients. This may be explained by the adverse influence of chemotherapy drugs’ side effects on dietary intake as observed in the high prevalence of nutrition impact symptoms including vomiting, nausea and loss of appetite during chemotherapy. A routine nutritional assessment during induction chemotherapy is recommended based on the results of this study. Further research should be done on the most effective intervention for these patients to improve their nutritional status and prevent deterioration in quality of life and further failure in treatment outcome.